Fishing Vessel Risk and Safety Analysis: A Bibliometric Analysis, Clusters Review and Future Research Directions - Soon Hyun Lee; Hyungju Kim; Sooyeon Kwon (Applied Sciences)
This study conducts a bibliometric analysis to evaluate the current research landscape and identify future directions in fishing vessel safety. Using the Scopus database, 285 relevant documents were collected and analyzed using the Biblioshiny app version 4.1 in the bibliometrix R package and VOSviewer version 1.6.20. The analysis generated an authors’ collaboration network, a three-field plot, and a keyword Thematic map, which were used for citation analysis, while VOSviewer was utilized to build networks between journals, articles, affiliations, countries, and keywords, enabling bibliographic coupling. The results identified four primary research clusters: Accident/Risk Analysis, Human Errors, Stability, and Operation. A detailed review of selected studies within these clusters was conducted, focusing on accident and risk factors, analytical methods, their strengths and weaknesses, and potential improvements. Based on these findings, a discussion was provided on future research directions in fishing vessel safety. The results suggest that future research should prioritize the integration of advanced technologies, enhancement of real-time monitoring capabilities, and promotion of international collaboration to ensure the safety of fishermen in hazardous environments.